Thermal expansion and polyamorphism of N2-C60 solutions - Manzhelii, V.G.; Dolbin, A.V.; Esel`son, V.B.; Gavrilko, V.G.; Gadd, ,G.E.; Moricca, S.; Cassidy, D.; Sundqvist, B. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2006)
The linear coefficients a(T) of N2–C60 solutions with 9.9% and 100% of the C60 lattice interstitialsfilled with N2 have been investigated in the interval 2.2–24 K. The dependence a(T) has a hysteresis suggesting co-existence of two types of orientational glasses in these solutions. The featuresof the glasses are compared. The characteristic times of phase transformations in the solutionsand reorientation of C60 molecules have been estimated.